Prognostic heterogeneity and clonal dynamics within distinct subgroups of myelodysplastic syndrome and acute myeloid leukemia with TP53 disruptions - Shyam A. Patel; Jan Cerny; William K. Gerber; Muthalagu Ramanathan; Asiri Ediriwickrema; Benjamin Tanenbaum; Lloyd Hutchinson; Xiuling Meng; Julie Flahive; Bruce Barton; Andrew J. Gillis‐Smith; Sakiko Suzuki; et al. (eJHaem, 2023)
Abstract TP53 aberrations constitute the highest risk subset of myelodysplastic neoplasms (MDS) and acute myeloid leukemia (AML). The International Consensus Classification questions the blast threshold between MDS and AML. In this study, we assess the distinction between MDS and AML for 76 patients with TP53 aberrations. We observed no significant differences between MDS and AML regarding TP53 genomics. Median overall survival (OS) was 223 days for the entire group, but prognostic discrimination within subgroups showed the most inferior OS (46 days) for AML with multihit allelic state plus TP53 variant allele frequency (VAF) > 50%. In multivariate analysis, unadjusted Cox models revealed the following variables as independent risk factors for mortality: AML (vs. MDS) (hazard ratio [HR]: 2.50, confidence interval [CI]: 1.4–4.4, p = 0.001), complex karyotype (HR: 3.00, CI: 1.4–6.1, p = 0.003), multihit status (HR: 2.30, CI 1.3–4.2, p = 0.005), and absence of hematopoietic cell transplant (HCT) (HR: 3.90, CI: 1.8–8.9, p = 0.0009). Clonal dynamic modeling showed a significant reduction in TP53 VAF with front‐line hypomethylating agents. These findings clarify the impact of specific covariates on outcomes of TP53‐aberrant myeloid neoplasms, irrespective of the diagnosis of MDS versus AML, and may influence HCT decisions.